2019
DOI: 10.1002/htj.21552
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an inertance pulse tube refrigerator using the particle swarm optimization algorithm

Abstract: In this study, a particle swarm optimization method is employed to find the optimal operating parameters and geometrical parameters, which maximize the coefficient of performance (COP) of an inertance pulse tube refrigerator (IPTR). The considered decision variables of the IPTR are the charging pressure, which varies from 15 to 25 bar, operating frequency varying from 20 to 60 Hz, geometrical parameters, such as diameter varying from 15.0 to 25.00 mm, and length varying from 40.0 to 70 mm of the regenerator; d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Response surface methodology (RSM) is an approach that can be applied for optimizing mechanical systems (Nariman et al, 2021) through several combinations of factor levels to build a regression model. A 1D analysis of the cryocooler (Panda and Rout et al, 2019) where an optimized COP for a fixed cold end temperature was reported. Even though many researchers have adopted RSM analysis, an optimization method and sensitivity analysis with CFD data for obtaining the lowest cold end temperature is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology (RSM) is an approach that can be applied for optimizing mechanical systems (Nariman et al, 2021) through several combinations of factor levels to build a regression model. A 1D analysis of the cryocooler (Panda and Rout et al, 2019) where an optimized COP for a fixed cold end temperature was reported. Even though many researchers have adopted RSM analysis, an optimization method and sensitivity analysis with CFD data for obtaining the lowest cold end temperature is lacking.…”
Section: Introductionmentioning
confidence: 99%